Profit or Pitfall? The Hidden Complexities of Transfer Pricing in International Business - Zhafirrah Rosalinda; Anisya Tri Maryati; Muhammad Farisz Noor Ikhsan; Deta Trinalti Oktavia (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study examines the hidden complexities of transfer pricing in international business, exploring both the strategic benefits and the potential pitfalls that multinational enterprises encounter in today's digital economy. Transfer pricing, while serving as an essential tool for tax planning and profit allocation, presents significant challenges related to compliance, regulatory uncertainty, and ethical considerations. Through a comprehensive review of contemporary literature and in-depth analysis of recent case studies, the research identifies key issues including profit shifting, manipulation of tax bases, and discrepancies in regulatory enforcement across jurisdictions. The study finds that, despite offering potential tax advantages, poorly managed transfer pricing practices can lead to substantial risks such as increased scrutiny from tax authorities, financial penalties, and reputational damage. Moreover, the research highlights the need for greater transparency and harmonization in global tax regulations to mitigate these risks and promote fair competition. By critically analyzing the evolving landscape of digitalization and its impact on transfer pricing mechanisms, this paper argues for the adoption of robust and adaptive regulatory frameworks that can effectively address the challenges posed by modern business models. The findings call on policymakers and international regulatory bodies to enhance cooperative efforts and refine guidelines that balance corporate tax planning with equitable revenue collection. Such measures are essential for ensuring market stability and preventing the adverse economic effects of aggressive tax avoidance strategies.